Practitioner Inquiry, Knowledge, and University Culture - Cochran-Smith, Marylin; Lytle, Susan (International Handbook of Self-Study of Teaching and Teacher Education Practices, 2004)
This chapter explores the relationships among practitioner inquiry, knowledge, and the cultures of universities. The chapter uses the term, “practitioner inquiry,” as a kind of conceptual umbrella to overview a number of di3ering forms of practitioner-based study of teaching, teacher education, and related issues. The chapter has three major parts. The first examines the discourse and terminology of practitioner inquiry, suggesting that the language used to describe it has been widely appropriated for many different contexts. The chapter argues, however, that it is not language alone that differentiates particular kinds of inquiry, nor is it ideological, political, or historical traditions alone. Rather, in order to understand the range and variation of practitioner inquiry, particular practitioner inquiry initiatives and their operating assumptions about how inquiry is related to knowledge, practice, and change must be examined. The chapter offers three different inquiry-knowledge-practice relationships as a way to sort these out. The second section of the chapter discusses the features and assumptions that most variants of practitioner inquiry share and that divide practitioner inquiry from many traditional forms of educational research. The chapter identifies the most common critiques of practitioner inquiry, particularly in relation to issues of epistemology, methodology, and politics. The final section considers the role of practitioner inquiry in the university. This section of the chapter draws on the authors’ own experiences working with teacher research and other inquiry communities within the contexts of large research universities Offer a period of more than 15 years. It explores the ethical, political, and practical dilemmas and contradictions that are created when teacher research and its underlying premises are taken seriously Offer a long period of time and within the culture of the university.
Keywords: formation des adultes; pratique pédagogique; résultat de recherche; utilisation des recherches; États-Unis